Pengaruh Live Streaming dan Content Marketing Terhadap Minat Beli Busana Online Produk Lozy Hijab Pada Tiktok Shop (Studi Pada Warga Malang) - Intan Anisa Rachmadyanty Wijaya; Yulis Nurul Aini; Fullchis Nurtjahjani (PENG: Jurnal Ekonomi dan Manajemen, 2026)
Live streaming and content marketing are important factors that influence consumer purchase intention. Live streaming can create a more intimate and convincing experience, while content marketing can attract attention and create connections with the audience. This study aims to determine the influence of live streaming and content marketing, both partially and simultaneously, on the purchase intention of Lozy Hijab products on TikTok Shop among residents of Malang City. This is a quantitative study comprising two independent variables live streaming and content marketing and one dependent variable, purchase intention. Data was collected through a questionnaire distributed to 96 residents of Malang City who are familiar with the Lozy Hijab brand and have an interest in purchasing it. This study employed purposive sampling techniques. Data analysis was conducted using multiple linear regression to measure the influence of the two variables on Purchase Intention. The results of the study indicate that Live Streaming and Content Marketing have a significant partial influence on Purchase Intention. Simultaneously, both variables influence purchase intention. However, there are other factors beyond live streaming and content marketing that also influence purchase intention. It can be concluded that live streaming and content marketing play an important role in influencing consumer interest in Lozy Hijab products. The company is advised to pay more attention to optimizing the implementation of live streaming and content marketing